2016
DOI: 10.2105/ajph.2015.302985
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of HIV-Related Stigma in Faith-Based Organizations

Abstract: Opportunities for connection with people living with HIV/AIDS tailored to the social characteristics of faith-based organizations may address HIV stigma in African American communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Having a higher education was associated with increased self-stigma. This finding was inconsistent with evidence suggesting that higher education was a protective factor against self-stigma (Coleman, Tate, Gaddist, & White, 2016;Galvan, Davis, Banks, & Bing, 2008;Sayles et al, 2008). A possible explanation for this contradiction might be that those with higher education levels may have higher work and social status, and thus, may feel less secure and afraid to disclose their health status for fear of loss of social status and jobs.…”
Section: Discussionmentioning
confidence: 70%
“…Having a higher education was associated with increased self-stigma. This finding was inconsistent with evidence suggesting that higher education was a protective factor against self-stigma (Coleman, Tate, Gaddist, & White, 2016;Galvan, Davis, Banks, & Bing, 2008;Sayles et al, 2008). A possible explanation for this contradiction might be that those with higher education levels may have higher work and social status, and thus, may feel less secure and afraid to disclose their health status for fear of loss of social status and jobs.…”
Section: Discussionmentioning
confidence: 70%
“…Our results support findings from other studies that demonstrated the important role African American churches can play in advancing HIV awareness and encouraging engagement in HIV testing, linkage to care and treatment. [21][22][23][24][25]28 Many clergy members in this study noted that HIV stigma was a barrier to successfully implementing HIV related programs in their churches-a challenge that is well documented in the literature. 25,[29][30][31] As cited elsewhere, 32 clergy in this study were aware of their potential positive social influence regarding HIV screening, prevention and care.…”
Section: Discussionmentioning
confidence: 81%
“…[7][8][9] More recently, African American churches have been ited resources, reluctance to discuss human sexuality in a faith setting, and insufficient knowledge about the epidemic. 19,20 While research indicates that African American clergy are willing to participate in HIV prevention activities within their congregations and offer HIV testing at their churches, [21][22][23][24][25] little research has explored how to most effectively engage African American clergy in enhancing outcomes along the HIV Care Continuum beyond HIV screening; these could include linkage and retention in HIV care and ultimately, suppression of HIV RNA. To address this gap, we conducted focus groups with African American clergy in Jackson, Mississippi to assess clergy knowledge of the HIV care continuum and their willingness to engage in activities that promote HIV diagnosis, linkage and retention in HIV care.…”
Section: Clergy Perspectives On Hiv Care Continuum -Nunn Et Almentioning
confidence: 99%
“…Besides access to multidisciplinary, interdisciplinary, and participatory programs and the strengthening of basic health care, government officials should go beyond medical science. They should investigate the denigration of women worldwide, as well as the economic disintegration in many countries that prevents childbearing women from getting adequate infrastructure and effective antiretroviral therapies 47–51…”
Section: The Role Of Medicinementioning
confidence: 99%